Invasive Staphylococcus Epidermidis Isolates are Highly Clonal and Distinct from Commensal Strains: Time for a New Paradigm in Infection Control?. (4th October 2017) - Dib, Rita Wilson; Numan, Yazan; Li, Xiqi; Kalia, Awdhesh; Raad, Issam; Shelburne, Samuel A
Abstract: Background: Staphylococcus epidermidis is a ubiquitous human commensal but also a leading cause of healthcare-assisted bloodstream infections (HABSI). Commensal S. epidermidis strains are genetically diverse. We used whole genome sequencing(WGS) to test the hypothesis that invasive S. epidermidis strains are genetically heterogeneous. Methods: S. epidermidis isolates that caused a clinically significant HABSI from unique patients at the MD Anderson Cancer Center were collected between 2013 and 2015. WGS was performed via Illumina Miseq followed by phylogenomics using kSNP. Clinical metadata was abstracted from the EMR. A cluster was defined as ≥ 3 strains that differed from each other by ≤ 40 single nucleotide polymorphisms (SNPs) over the ~2.5 million base pair genome. Results: Complete genomic data was generated for 176 strains which consisted of 27 different sequence types (ST). Six clusters were identified comprised of 34 (ST5 subclone A), 32 (ST2), 29 (ST5 subclone B), 16 (ST83), 6 (ST22), and 5 (ST210) strains which accounted for 70% of the total isolates (Figure). The median number of SNPs separating two strains within a particular cluster was 15. 50 strains had ≤ 10 SNPs relative to their nearest relative, including 26 strains with 0 or 1 SNP. Strains from ST5 subclone B were significantly more likely to be isolated from patients with leukemia (a separate clinical service at our institution) whereas non-clustering strains were more likely to cause disease in patients with solid cancers ( P < 0.001 by χ 2 ). Compared with other clusters, ST5 subclone B strains were isolated later in the study period ( P = 0.006 by ANOVA) indicating evolution and expansion from ST5 subclone A. S. epidermidis was identified in 93 skin metagenomic samples from the Human Microbiome Project (i.e., commensals), but only 2/93 were an ST that formed a cluster in our study (one each of ST5 and ST210). Conclusion: Invasive S.epidermidis isolates mainly occur as clusters of strains that are identical or nearly identical via WGS and are distinct from S. epidermidis colonizing the skin of healthy humans. These data indicate that transmission of S. epidermidis adapted to cause HABSI is occurring in the healthcare setting and could be amenable to infection control prevention. Disclosures: I. Raad, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant; Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Raad is a s and Shareholder, Licensing agreement or royalty